Penerapan Metode TOPSIS Dalam Penentukan Tempat Wisata Alam Terbaik di Bengkulu - Purnama, Soni Ayi (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2024)
Bengkulu is a province in Indonesia which is in the southern part of Sumatra. Bengkulu has a number of interesting natural tourist attractions and is often a favorite destination for tourists. There are many tourist attractions in Bengkulu, ranging from natural attractions, zoos, mountains and others. In this research, the author tries to determine which tourist attractions are the favorite or best tourist attractions that are visited by local residents and residents from outside the Bengkulu area. In this research the author used the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method with data collection using a Likert Scale approach. The criteria used in this research are 6 criteria consisting of View (C1), Cleanliness (C2), Security (C3), Comfort (C4), Facilities (C5) and Access (C6). From the data processing that has been carried out, the result is that the tourism that is considered to be the best tourism in Bengkulu is Long Beach tourism with the highest preference value, namely 0.82.